88.1k views
3 votes
Note: Enter your answer and show all the steps

that you use to solve this problem in the space
provided
What is the solution to the equation?
2x + 10 – 6 = 2

User AdamOutler
by
5.6k points

1 Answer

3 votes

The solution to given equation 2x + 10 -6 = 2 is x = -1

Solution:

Given that the equation is:

2x + 10 -6 = 2

We have to find solution to the equation. Which means we have to solve and find value of "x"

Let us first simplify the given equation

2x + 10 - 6 = 2

Let us use BODMAS rule to perform sequence of arithmetic operations

According to BODMAS rule, if an expression contains brackets ((), {}, []) we have to first solve or simplify the bracket followed by of (powers and roots etc.), then division, multiplication, addition and subtraction from left to right

So first perform subtracting 6 from 10

2x + 4 = 2

Let us move the term "4" from L.H.S to R.H.S

2x = 2 - 4

Now perform addition of 2 and -4

2x = -2


x = (-2)/(2)

Now perform division operation

x = -1

Thus the solution to given equation is x = -1

User Paul Bruno
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.